2014
DOI: 10.1007/s13213-014-0929-5
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting spatiotemporal patterns and environmental drivers of diversity and community structure of ammonia oxidizers, denitrifiers, and anammox bacteria in sediments of estuarine tidal flats

Abstract: The spatial and temporal patterns of diversity, community structure, and their drivers are fundamental issues in microbial ecology. This study aimed to investigate the relative importance of spatial and seasonal controls on the distribution of nitrogen cycling microbes in sediments of estuarine tidal flats, and to test the hypothesis that metals impact the distribution of nitrogen-cycling microbes in the coastal system. Two layers of sediment samples were collected from three estuarine tidal flats of Laizhou B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 69 publications
1
5
3
Order By: Relevance
“…In the BS and NYS, algal blooms generally peak during May to July (Wei et al, 2004), and thus the organism is prevalent in that season. In contrast to other works (Magalhães et al, 2008;Mills et al, 2008;Fernandes et al, 2012;Yang et al, 2015;Yu et al, 2018), we observed that the Betaproteobacteriarelated nosZ group comprised a substantial fraction of the overall nosZ community detected in the Huanghe River estuary site. Betaproteobacteria is commonly detected in the freshwater and estuarine systems, such as Columbia River estuary (Crump et al, 1999), Changjiang River estuary (Feng et al, 2009), and Zhujiang (Pearl) River estuary (Liu et al, 2015).…”
Section: Distribution and Environmental Drivers Of Benthic Nosz -Denicontrasting
confidence: 99%
See 3 more Smart Citations
“…In the BS and NYS, algal blooms generally peak during May to July (Wei et al, 2004), and thus the organism is prevalent in that season. In contrast to other works (Magalhães et al, 2008;Mills et al, 2008;Fernandes et al, 2012;Yang et al, 2015;Yu et al, 2018), we observed that the Betaproteobacteriarelated nosZ group comprised a substantial fraction of the overall nosZ community detected in the Huanghe River estuary site. Betaproteobacteria is commonly detected in the freshwater and estuarine systems, such as Columbia River estuary (Crump et al, 1999), Changjiang River estuary (Feng et al, 2009), and Zhujiang (Pearl) River estuary (Liu et al, 2015).…”
Section: Distribution and Environmental Drivers Of Benthic Nosz -Denicontrasting
confidence: 99%
“…The coastal sites, especially near the Huanghe River estuary, held higher diversity and distinct community structure of nosZ gene from central sites, probably because freshwater and sediment inputs from the river brought in terrigenous nosZ phylotypes, and on the other hand, some specifi c nosZ phylotypes could be evolved in the anthropogenic perturbation-dominated coastal setting. Similar to previous studies of coastal and marine nosZ -denitrifi ers (Magalhães et al, 2008;Mills et al, 2008;Fernandes et al, 2012;Yang et al, 2015;Yu et al, 2018), all nosZ sequences detected are related to proteobacteria, and Alphaproteobacteria formed the most dominant and ubiquitous putative nosZ group in the BS and NYS sediments, suggesting that this group was well adapted to coastal marine sediments and likely contributed importantly to nitrogen removal in the environments. Within Alphaproteobacteria, N .…”
Section: Distribution and Environmental Drivers Of Benthic Nosz -Denisupporting
confidence: 86%
See 2 more Smart Citations
“…The relative abundance of each T‐RF was calculated as the ratio of the peak area of that T‐RF to the total peak area of all of the T‐RFs detected for a given sample. Based on the T‐RFLP data, alpha diversity estimators (Shannon's index, H ; Simpson's index, 1/ D ; and evenness, E ) were calculated using an online diversity calculator (http://www.changbioscience.com/genetics/shannon.html; Yang et al, ).…”
Section: Methodsmentioning
confidence: 99%